INNOVATIVE AND SUSTAINABLE SOLUTIONS IN AGRICULTURE HAS BEEN A PRIORITY FOR SCIENCE - Carvalho , Walter Augusto Fonseca de; Carniatto, Irene; Ferreira dos Santos, Reginaldo (International Journal of Environmental Resilience Research and Science, 2023)
Agronomic researches are one of the main possibilities to ensure food security for this and for future generations to provide sustainable agriculture. In this context, it is with great pleasure that we present the newest special edition of the “International Journal of Environmental Resilience Research and Science”, entitled Agronomy and Sustainability. This edition is the result of both III International Symposium on Agronomy and Sustainability at UNASP-EC, and a partnership among Brazilian Universities: Adventist University Center of São Paulo Campus Engenheiro Coelho -UNASP, Western Paraná State University -UNIOESTE, Assis Gurgacz Foundation University Center–FAG, and with the Universidad Adventist de Chile -UNACH. The search for innovative and sustainable solutions in agriculture has been a priority for researchers around the world. In this context, our scientific journal presents in this issue a series of papers that address different aspects of sustainable agronomic research.